United Nations Disarmament Yearbook 1991 - United Nations Office for Disarmament Affairs (United Nations, 1991)
The volume 16 compiles the disarmament resolutions and decisions of the forty-sixth session of the General Assembly, the voting patterns in the General Assembly and the First Committee report and dates of their adoption. It summarizes developments and trends in 1991 on key issues of multilateral consideration at the international and regional levels. Reviews the activity of the forty-sixth session of the General Assembly, the Conference on Disarmament and the Disarmament Commission. Contains a timeline that highlights events in multilateral disarmament in 1991.